2014
DOI: 10.1089/dna.2014.2573
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphisms in Interleukin-23 Receptor and Susceptibility to Coronary Artery Disease

Abstract: As a key element in the T-helper 17 (Th17) cell-mediated inflammatory process, interleukin-23 receptor (IL-23R) may play a crucial role in the pathogenesis of atherosclerosis. Single nucleotide polymorphisms (SNPs) in IL-23R have been studied in several diseases. However, its association with coronary artery disease (CAD) remains unclear. This study examined whether genetic polymorphisms in IL-23R were associated with susceptibility to CAD. Two IL-23R SNPs, rs1884444 and rs6682925, were genotyped in 462 CAD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
(23 reference statements)
0
22
0
Order By: Relevance
“…IL-23 has been shown to participate in many inflammatory diseases, such as inflammatory bowel disease, psoriasis and coronary heart disease [6,7,8]. There are emerging evidence suggests that HMGB1-TLR4-IL-23/IL-17 axis plays a critical role in initiating and enhancing the inflammatory responses and ROS production during myocardial I/R [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…IL-23 has been shown to participate in many inflammatory diseases, such as inflammatory bowel disease, psoriasis and coronary heart disease [6,7,8]. There are emerging evidence suggests that HMGB1-TLR4-IL-23/IL-17 axis plays a critical role in initiating and enhancing the inflammatory responses and ROS production during myocardial I/R [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…23,24) Zhang, et al found IL-23R rs6682925T/C polymorphism acted as a risk factor in process of atherosclerosis. 25) Mir-3162-3p may be an important factor involved in the formation of atherosclerosis by modulating IL-23R.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiologic studies have observed that polymorphisms in the genes encoding interleukin-1 receptor antagonist, such as , are associated with the development of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One animal experimental study has shown that several cytokines play a key role in the development of CAD (Kleemann et al, 2008). Several previous epidemiology studies have shown that polymorphisms in several cytokines, including interleukin-6 (IL-6), , are involved in the pathogenesis of CAD (Zhang et al, 2011;Huang et al, 2013;Opstad et al, 2011Opstad et al, , 2013Galimudi et al, 2014;He et al, 2014;Zhang et al, 2014). However, the results of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%